2015
DOI: 10.1016/j.bmcl.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Post-HTS case report and structural alert: Promiscuous 4-aroyl-1,5-disubstituted-3-hydroxy-2 H -pyrrol-2-one actives verified by ALARM NMR

Abstract: Despite its wide use, not every high-throughput screen (HTS) yields chemical matter suitable for drug development campaigns, and seldom are ‘go/no-go’ decisions in drug discovery described in detail. This case report describes the follow-up of a 4-aroyl-1,5-disubstituted-3-hydroxy-2H-pyrrol-2-one active from a cell-free HTS to identify small-molecule inhibitors of Rtt109-catalyzed histone acetylation. While this compound and structural analogs inhibited Rtt109-catalyzed histone acetylation in vitro, further wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 95 publications
2
28
0
Order By: Relevance
“…ALARM NMR and ALARM MS have been employed in the industrial setting to both validate pre-clinical candidates 22 and to identify nonspecific reactive compounds 23 . We have previously shown that the assay can also flag non-reactive modulators of La antigen conformation; specifically, a class of 4-aroyl-1,5-disubstituted-3-hydroxy-2 H -pyrrol-2-ones we encountered during an HTS campaign targeting the HAT Rtt109 24 . Compounds with this chemotype did not show evidence of thiol reactivity in several experiments, including an ultra-performance LC (UPLC)-MS GSH adduct assay, but were ALARM NMR-positive independent of DTT, a pattern consistent with nonspecific protein perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…ALARM NMR and ALARM MS have been employed in the industrial setting to both validate pre-clinical candidates 22 and to identify nonspecific reactive compounds 23 . We have previously shown that the assay can also flag non-reactive modulators of La antigen conformation; specifically, a class of 4-aroyl-1,5-disubstituted-3-hydroxy-2 H -pyrrol-2-ones we encountered during an HTS campaign targeting the HAT Rtt109 24 . Compounds with this chemotype did not show evidence of thiol reactivity in several experiments, including an ultra-performance LC (UPLC)-MS GSH adduct assay, but were ALARM NMR-positive independent of DTT, a pattern consistent with nonspecific protein perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…Actual drug discovery programs do not rely on just one technique but utilize multiple sources of information to rule out non-stoichiometric inhibition. [29,51,55] However, on its own, such a subtractive approach is not always sufficient to unambiguously demonstrate stoichiometric inhibition, which should be proven by positive evidence.…”
Section: Experimental Identification Of Nonstoichiometric Inhibitors mentioning
confidence: 97%
“…[49] Another technique to detect aggregation of a compound is nuclear magnetic resonance (NMR), which either analyzes the signal from the compound itself [50] or uses the conformational distortion of the human La antigen as a surrogate readout in what is called ALARM NMR. [18,51] An indirect approach compares compound potency at different concentrations of enzyme [25,52]; bellshaped dose-response curves in cellular assays are another warning signal. One of several possible explanations is the failure of colloidal aggregates to enter intact cells.…”
Section: Colloidal Aggregationmentioning
confidence: 99%
“…Other FDA‐approved drugs are not ideal candidates for further development . Many chemotherapy drugs that require infusion, such as the bright blue compound mitroxantrone, an agent which has a variety of activities in cells, have limited solubility and may induce nonspecific aggregation of the protein or assay reagents in high throughput screening .…”
Section: Repurposing As a Path To New Drugsmentioning
confidence: 99%